L'Arbre du Prophète. Prophétisme, ancestralité et politique au Maghreb - Houari Touati (Revue des Mondes Musulmans et de la Méditerranée)
Ibn Abî Mahallî is, without any doubt, the most important prophetic figure the Maghrib has known since Ibn Tûmart. Historians have been principally interested in Ibn Abî Mahallî's political actions and, only secondly, in his many writings. Therefore, an analysis of this fiery Saharian scholar's doctrinal system which he developed in order to justify his actions as mahdi, largely remains to be done. The present article contributes, in particular, towards unraveling the genealogical intricacies.